Konsep Kekuasaan Dalam Fiqh Dusturiyah dan Relevansinya Terhadap Sistem Ketatanegaraan Indonesia: Fiqh Dusturiyah, Siyasah Dusturiyah, Popular Sovereignty, Constitutional Democracy - Abisali Nasution; Alfian Fauzi Priambodo; Achmad Farraj Rabbani; Aulia Khairuddin Limbong; Alaydrus Albuchori Ritonga (Albayan Journal of Islam and Muslim Societies, 2025)
Indonesia as a rule-of-law state requires state administration to be based on legislation, making the study of the concept of power in Fiqh Dusturiyah relevant for understanding the convergence of Islamic values and constitutional democracy. This study aims to explain the concept of power in Siyasah Dusturiyah, assess its relevance to the principle of popular sovereignty in Indonesia, and identify its contribution to the understanding of constitutional democracy. The method used is qualitative with a library research approach and content analysis of primary data (works by Al-Mawardi, Ibn Taymiyyah) and secondary data (1945 Constitution, academic journals). The results show that power in Fiqh Dusturiyah is an trust (amanah) with a three-domain division (legislative, executive, judicial) based on shura, justice, and maṣlaḥah. In conclusion, Fiqh Dusturiyah can enrich Indonesia's constitutional democracy ethically without changing the state's institutional format.